An experimental study exploring the effects of predict-observe-explain method supported with simulations - Tuysuz, Ayşegül; Özdemİr, Ömer faruk (Research in science & technological education, 2025)
Since the early 20th century, research has been conducted on how to ensure optimal learning. With the developing and changing technology, different teaching methodologies and environments such as simulation, virtual lab, and interactive video have created the opportunity for educators to use them for this purpose. Nowadays, these are applied alone or in combination with different methods according to the student's needs, subject, and environment. This study investigated the effect of using predict-observe-explain (POE) tasks enriched with computer simulations for the explanation part on 9th graders' physics achievement. Additionally, the possible role of gender in this effect was examined. The study was conducted with 107 9th graders (53 males and 54 females) from a high school in Turkey. The experimental group (n = 49) received POE tasks enriched with computer simulations, while the control group (n = 58) received traditional POE tasks. A quasi-experimental design with a pretest-posttest control group was used for his purpose. The results showed that the experimental group outperformed the control group regarding physics achievement. Furthermore, the effect of the intervention was found to be equally effective for both females and males. These findings suggest that the use of POE tasks enriched with computer simulations can be an effective instructional strategy to enhance students' physics achievement.